EXPLORING STUDENTS’ ENGLISH VOCABULARY LEARNING EXPERIENCES IN MERDEKA BELAJAR CURRICULUM: THE CASE OF VOCATIONAL HIGH SCHOOL IN INDONESIA - Anggraini, Erina Setyo; Kristiawan, Dana Yudha; Rahman, Abd. - (ELITERATE : Journal of English Linguistics and Literature Studies, 2025)
This study explores the English vocabulary learning experiences of 11th-grade students in a Vocational High School in East Java, Indonesia, within the framework of the Merdeka Belajar Curriculum. While previous research has focused on teaching strategies and curriculum implementation from the teacher's perspective, this study emphasizes students' voices, particularly how they engage with vocabulary learning in a hospitality context. Using a qualitative case study design, data were collected through classroom observations, semi-structured interviews, and questionnaires, and analyzed using Braun and Clarke’s thematic analysis framework.Findings reveal three major themes: (1) Learner Agency and Personalization, where students exhibit autonomy in selecting vocabulary relevant to their interests and future careers; (2) Digital Literacy Through Vocabulary Acquisition, as students increasingly use digital platforms such as YouTube, games, and social media to enhance vocabulary learning; and (3) Navigation Challenges in Autonomous Learning, including difficulties in evaluating word relevance, managing abundant resources, and lacking standardized vocabulary lists. Quantitative data from the Likert-scale questionnaire support the qualitative findings, indicating high motivation and positive perceptions toward the curriculum, yet also highlighting issues such as limited guidance and time constraints. The study concludes that while the Merdeka Curriculum fosters independent and contextual vocabulary learning, ongoing support in terms of teacher facilitation, curriculum alignment, and access to appropriate learning resources is essential for maximizing student outcomes in vocational education.